Probing the acidity of carboxylic acids in protic ionic liquids, water, and their binary mixtures: activation energy of proton transfer - Shukla, Shashi Kant; Kumar, Anil (Journal of Physical Chemistry B, 2013)
Acidity functions were used to express the ability of a solvent/solution to donate/accept a proton to a solute. The present work accounts for the acidity determination of HCOOH, CH3COOH, and CH3CH2COOH in the alkylimidazolium-based protic ionic liquids (PILs), incorporated with carboxylate anion, water, and in a binary mixture of PIL and water using the Hammett acidity function, H-0. A reversal in the acidity trend was observed, when organic acids were transferred from water to PIL. It was emphasized that an increased stabilization offered by PIL cation toward the more basic conjugate anion of organic acid was responsible for this anomalous change in acidity order in PILs, which was absent in water. The greater stabilization of a basic organic anion by PIL cation is discussed in terms of the stable hard-soft acid base (HSAB) pairing. A change in the H-0 values of these acids was observed with a change in temperature, and a linear correlation between the ln H-0 and 1/T was noted. This relationship points toward the activation energy of proton transfer (E-a,E-H+), a barrier provided by the medium during the proton transfer from Bronsted acid to indicator. The H-0 function in binary mixtures points to the involvement of pseudosolvent, the behavior of which changes with the nature and concentration of acid. The presence of the maxima/minima in the H-0 function is discussed in terms of the synergetic behavior of the pseudosolvent composed of the mixtures of aqueous PILs.